MARKETING MIX EFFECT OF INTEREST TO VISIT IN THE LAKE TOBA (CASE STUDY: BALIGE AND SAMOSIR) - Vera Clara Simanjuntak (STIE Binaniaga, 2016)
The natural beauty of Lake Toba has become popular tourism area, both on national and international scales. BPS data show before the pre-crisis the number of tourists reached about average 500 thousand per year, after the crisis the number of visits never 100 thousand per year. The tourism objects are not managed and the variety of tourism products are not developed, make tourists less interested. Bad marketing factors were believed the cause of problems of sales travel services. The research was conducted using by survey with correlation approach. The questionnaire asked to measure tourists response to marketing mix and survey research responses to measure the effect of marketing mix against interest visiting to Lake Toba. The technique used to obtain data marketing mix and interests through questionnaires. Analysis to measure the effect using the Pearson product moment correlation. Interest in visiting using Likert scale options. Questionnaire made by own and performed by field trials with the respondents as many as 15 people. The test result has 1 (one) invalid point on the promotion of indicators with score of 0.213 and one (1) item of physical evidence with score of 0.302. Conditions of acceptance of the validity if rhit > rtab then 0.213 < 0.553 and 0.302 < 0.553 and 15 variable instruments of interest visiting in Lake Toba area, everything is valid, because the score results with r above 0.553. Scale reliability coefficient calculated for the marketing mix of 0.979, and interest amounting to 0.905. There are influences of marketing mix 7P against of interest visiting to Lake Toba, either partially or simultaneously. The size effect the indicators of the marketing mix to interest visiting Lake Toba, namely: the product of 64.5%, 62.4% of the price, the place of (59.4%), physical evidence of 57.2%, promotion by 50.7%, the person or the quality of human resources by 12% and the smallest and most influential is the process by 9.4%. Great influence of the marketing mix (P7) all the elements together or simultaneous to the interest visiting Lake Toba as much 68.8%. The marketing strategy using the marketing mix simultaneously to contribute has greater influence than individually.Keyword: marketing, promotion mix, sales promotion.